Progresive muscle relaxtion (PMR) untuk menurunkan gangguan pola tidur - Sari, Devi Ratna; Wahyudi , Wahid Tri; Hermawan, Dessy (JOURNAL OF Mental Health Concerns, 2023)
Background: Over a period of nearly 50 years (1971-2018), the percentage of Indonesia's elderly population has roughly doubled. In 2018, the percentage of elderly people reached 9.27 percent or around 24.49 million people (BPS, 2018). In 2019 there was an increase, namely the percentage of elderly people, namely to 9.6 percent (25 million), where there were around one percent more elderly women than elderly men (10.10 percent compared to 9.10 percent). Of all the elderly in Indonesia, the young elderly (60-69 years) far dominate with a magnitude of 63.82 percent, then followed by the middle elderly (70-79 years) and the old elderly (80+ years) with a magnitude of 27 each. 68 percent and 8.50 percent. Purpose: Providing gerontic nursing care with the main nursing problem of sleep pattern disturbances with Progressive Muscle Relaxtion (PMR) in Sukajaya Lempasing Village in 2023 Method: This type of research uses descriptive qualitative research, this research uses descriptive research methods in the form of case studies with the Nursing Care approach, which includes assessment, nursing diagnosis, planning, implementation, and evaluation. Results: From the results of studies conducted on Mrs. E and Mrs. R, sleep pattern disorders were obtained. The data obtained by the patient named Mrs. R is female aged 65 and 70 years. Conclusion: The implementation study for 3 days obtained partially resolved results, which were characterized by an increase in elderly sleep duration. The results of the evaluation conducted for three days showed that all problems could be resolved.  Keywords: Elderly; Nursing Care; Progressive Muscle Relaxtion (PMR); Sleep Pattern Disturbance. Pendahuluan: Selama kurun waktu hampir 50 tahun (1971-2018), persentase penduduk lansia Indonesia meningkat sekitar dua kali lipat. Pada tahun 2018, persentase lansia mencapai 9,27 persen atau sekitar 24,49 juta orang (BPS, 2018). Pada Tahun 2019 terjadi peningkatan yakni persentase lansia yakni menjadi 9,6 persen (25 juta-an) di mana lansia perempuan sekitar satu persen lebih banyak dibandingkan lansia laki-laki (10,10 persen banding 9,10 persen). Dari seluruh lansia yang ada di Indonesia, lansia muda (60-69 tahun) jauh mendominasi dengan besaran yang mencapai 63,82 persen, selanjutnya diikuti oleh lansia madya (70-79 tahun) dan lansia tua (80+ tahun) dengan besaran masingmasing 27,68 persen dan 8,50 persen. Tujuan: Memberikan asuhan keperawatan gerontik dengan masalah keperawatan utama gangguan pola tidur dengan Progresive Muscle Relaxtion (PMR) di Desa Sukajaya Lempasing Tahun 2023 Metode: Jenis penelitian ini menggunakan penelitian deskriptif kualitatif, penelitian ini menggunakan metode penelitian deskriptif dalam bentuk studi kasus dengan pendekatan Asuhan Keperawatan, yang meliputi pengkajian, diagnosa keperawatan, perencanaan, pelaksanaan, dan evaluasi. Hasil: Dari hasil pengkajian yang dilakukan pada Ny. E dan Ny. R didapatkan gangguan pola tidur. Data yang didapatkan pasien bernama Ny. R berjenis kelamin Perempuan berusia 65 dan 70 tahun. Simpulan: Kajian implementasi selama 3 hari didapat hasil sebagian masalah teratasi, yang ditandai dengan meningkatnya durasi tidur lansia. Hasil evaluasi yang dilakukan selama tiga hari menunjukkan semua masalah dapat teratasi.